Distributed connectivity preservation of a team of single integrator agents subject to measurement error - Salehisadaghiani, F.; Ajorlou, A.; Aghdam, A. G. (2011 IEEE International Symposium on Computer-Aided Control System Design (CACSD), 2011)
This paper deals with the connectivity preservation of multi-agent systems with state-dependent error in distance measurement. It is assumed that upper bounds on the measurement error and also its rate of change as a function of distance are available. A general class of distributed control strategies is then proposed for the distance-dependent connectivity preservation of the agents in the network. It is shown that if two neighboring agents are initially located at a distance closer than the required connectivity range, they are guaranteed to remain in the connectivity range at all times. The effectiveness of the proposed control strategies in consensus and containment problems is demonstrated by simulation.